2021
DOI: 10.7759/cureus.16834
|View full text |Cite
|
Sign up to set email alerts
|

Is Isotretinoin in Acne Patients a Psychological Boon or a Bane: A Systematic Review

Abstract: Acne vulgaris is a frequently encountered dermatological condition in clinical practice. Isotretinoin is one of the drugs prescribed for this condition. However, it is unclear whether the use of this drug worsens or improves the psychological effects in an acne patient and whether it is advisable to use this drug commonly. This systematic review aims to assess the relationship between Isotretinoin and psychiatric side effects in acne patients. A literature search was conducted using PubMed, Cochrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…12 For example, the evidence that isotretinoin is associated with an increased of suicide, as reported anecdotally, is poor. 13 Observational studies have in general been negative; when they have been positive, confounding by indication has been likely, since acne itself is associated with an increased risk. Despite this, the association has been widely accepted, although there have been contradictory statements.…”
Section: Observational Studies In Pharmacovigilancementioning
confidence: 99%
“…12 For example, the evidence that isotretinoin is associated with an increased of suicide, as reported anecdotally, is poor. 13 Observational studies have in general been negative; when they have been positive, confounding by indication has been likely, since acne itself is associated with an increased risk. Despite this, the association has been widely accepted, although there have been contradictory statements.…”
Section: Observational Studies In Pharmacovigilancementioning
confidence: 99%
“…1,4,5 The exact association remains controversial, though isotretinoin is known to cross the blood-brain barrier and bind to retinoic acid receptors in the brain. 2,[6][7][8] In addition to treatment for acne, isotretinoin is a vital component of high-risk neuroblastoma treatment. Previous studies have shown it reduces the risk for relapse and improves overall survival.…”
Section: Isotretinoin-induced Psychosis In a Child On Treatment For H...mentioning
confidence: 99%
“…Isotretinoin, a retinoid authorized by the FDA in 1982, is one of the most efficient treatments for acne [ 5 ]. Reduced keratinization, reduction of the inflammatory response, and limited inhibition of sebaceous gland activity are the impacts of isotretinoin on acne vulgaris [ 6 ].…”
Section: Introductionmentioning
confidence: 99%